Identifying recent captive escapees of Rainbow Lorikeets (Trichoglossus moluccanus) at different stages of the pet-release pathway - Hill, Katherine G.W.; Delean, Steven; Robinson, Susan A.; Hall, Tony; Tyler, Jonathan J.; Stringham, Oliver C.; Cassey, Phillip (Frontiers in Ecology and Evolution, 2025)
IntroductionRainbow Lorikeets (Trichoglossus moluccanus) are a highly desirable bird in Australian pet trade and consequently have established invasive populations outside their native range. These birds are aggressive, outcompete native species, and cause significant damage to agriculture. Invasive populations have not been impacted by existing management practices, and it is unclear if their persistence is due to their high reproductive success in the wild, or from regular escapes from captivity.MethodsWe tested the ability of stable isotope analysis to identify recently escaped captive Rainbow Lorikeets in wild populations within Australia. We compared the stable carbon (δ13C) and nitrogen (δ15N) isotopes of captive birds to three wild populations at different stages of the pet-release pathway: (i) birds within their native distribution; (ii) a newly established population; and (iii) a large invasive population.ResultsWe found evidence of two escaped captive birds in the newly established population due to the higher and more variable δ13C, which is likely driven by the consumption of nectar supplements. The invasive population had a similar isotopic niche area to the native population; potentially indicating the invasive birds have adapted to the environment and learnt to consume a large variety of local food sources, therefore reducing the effectiveness of detecting recent escapees.DiscussionTherefore, for contained wild populations with small isotopic niches, stable isotope analysis can be a useful tool to identify captive escapees and can inform management of invasive species incursions.